Sinetron Religius: Sinetron Islami? - Muzayin Nazaruddin (Program Studi Ilmu Komunikasi, 2008)
In 2005-2007, Indonesian electronic cinemas (soup operas) full of religious- mystique contents. This genre usually named as religious or Islamic electronic cinema. These electronic cinemas are popularly considered representing religiosity and Islam. So, the question will be answered by this study is: in these electronic cinemas, what signifying practices which considered as the representation of religiosity and Islam? Answering this question, author applied Barthes's semiotics. Some research outcomes were resulted. First, there were more than 44 titles of religious electronic cinemas during 2005-2007. Second, three categories of these cinemas: the story of sinner which being tortured, the story of the successful tough, and the story the sinner which repent. Third, four signifying practices used to show that the content of these electronic cinemas are matching with Islamic doctrine: the titles use Islamic idioms, the resource of stories claimed as fact, use popular Islamic preachers, the narrative is Islamic sermon.